Realization of Lodging Tolerance in the Aromatic Grass, Cymbopogon khasianus Through Ploidy Intervention - Vimala, Yerramilli; Lavania, Umesh Chandra; Singh, Madhavi; Lavania, Seshu; Srivastava, Sarita; Basu, Surochita (Frontiers in Plant Science, 2022)
Artificial polyploidy that brings about increase in cell size confers changes in histo-morphology leading to altered phenotype, causing hanges in physiological attributes and enhanced concentration of secondary metabolites. The altered phenotype is generally a manifestation of tissue hardiness reflected as robust plant type. Based on a case study undertaken on an industrially important grass, Cympopogon khasianus (2n=60) valued for its citral rich essential oil, here we report that the artificial poplyploidy not only brings about enhancement in concentration of essential oil but also facilitates lodging tolerance. The latter is contributed by ploidy mediated changes that occur to the cells and tissues in various plant organs by way of increased wall thickening, tissue enhancement and epidermal depositions that enable robust features. An exhaustive illustrated account covering various micro- / macro-morphological, skeletal and histochemical features constituting growth and development vis-a-vis ploidy mediated changes is presented highlighting the novelties realized on account of induced polyploidy.